Microsoft Windows XP: Visual Quickstart Guide - Fehily, Chris (Peachpit Press, 2011)
What Windows XP Does The Two Versions of Windows XP What's New in Windows XP If You're Upgrading to Windows XP If You're Switching Over from a Macintosh About This Book